A study on factors influencing the effectiveness of training at Petronas Leadership Centre, Bangi / Yusafika Mohd Yusof - Mohd Yusof, Yusafika (Faculty of Business and Management, 2018)
The effectiveness of a training program must be assessed as it is a critical aspect in ensuring investment is made to improve the knowledge, skills, and positive attitude of employees towards their work in order to bring positive results to the organization, particularly government organizations that provide service to the community and country. The primary objective of this research is to analyze the environmental factors (superior support, opportunity to perform, and organizational learning culture) that affect the effectiveness of training in the context of training center in PETRONAS Leadership Centre (PLC), Bangi. Therefore, this study was conducted on 108 of staff from PLC. The results from this study indicated that only two work environment elements which are superior support and opportunity to perform positively contributed to the effectiveness of training. However, the element of organizational learning culture does not have any unique contribution on training effectiveness as it does not significant.